MODERN LIFESTYLE AND DYNAMICS OF READY-TO-EAT FOOD CONSUMPTION - Darmawan, Didit; Rizqullah, Muhammad Iqbal (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2026)
This study aims to analyze the influence of modern lifestyles on changes in ready-to-eat food consumption patterns and to identify factors affecting consumer decisions to choose these products. The research employs a qualitative literature study with a content analysis approach, drawing upon various relevant scholarly sources. The findings indicate that urbanization, shifts in family structure, time constraints, and advancements in food technology have driven a transformation in consumption patterns toward more convenient ready-to-eat products. Convenience emerges as the primary value sought by consumers, particularly among urban workers and younger generations. However, consumer decision-making is multidimensional, influenced by factors including price, taste, health awareness, social influence, marketing, availability, packaging, brand trust, emotional attachment, product innovation, and seasonal considerations. Consumers continuously negotiate between frequently conflicting factors, such as the desire for convenience versus healthiness, or affordability versus palatability. The implications of this study encourage manufacturers to innovate toward healthier products, marketers to develop more nuanced consumer segmentation strategies, and policymakers to formulate regulations supporting healthy consumption choices. Enhancing consumer awareness and nutritional literacy is also essential to enable more balanced decision-making.